2011
DOI: 10.1007/s11661-011-0957-8
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Creep Rupture Strength of Ferritic/Austenitic Dissimilar Weld Joints of Different Grades of Cr-Mo Ferritic Steels

Abstract: Evaluations of creep rupture properties of dissimilar weld joints of 2.25Cr-1Mo, 9Cr-1Mo, and 9Cr-1MoVNb steels with Alloy 800 at 823 K were carried out. The joints were fabricated by a fusion welding process employing an INCONEL 182 weld electrode. All the joints displayed lower creep rupture strength than their respective ferritic steel base metals, and the strength reduction was greater in the 2.25Cr-1Mo steel joint and less in the 9Cr-1Mo steel joint. Failure location in the joints was found to shift from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The situation becomes even more complex in the case of dissimilar welds, i.e. the welded joints between chemically different steels which are very frequent in power engineering [5][6][7][8]. For instance, the dissimilar welds combined of lower and higher chromium ferritic steels, such as T24/T92 welded joints can be used in a number of steam generator circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The situation becomes even more complex in the case of dissimilar welds, i.e. the welded joints between chemically different steels which are very frequent in power engineering [5][6][7][8]. For instance, the dissimilar welds combined of lower and higher chromium ferritic steels, such as T24/T92 welded joints can be used in a number of steam generator circuits.…”
Section: Introductionmentioning
confidence: 99%
“…The only possible reason which would help increasing the life of three layer welds is gradient in coefficient of thermal expansion. It has been reported that the presence of inhomogeneous microstructure across the interface develop stress concentration and stress triaxiality which also promotes the failure of dissimilar weld joints [7]. Similarly, in the three and single layer welds apart from inhomogeneous microstructure across the weld interface, another factor which contributes to stress concentration is the mismatch in CTE value.…”
Section: Introductionmentioning
confidence: 99%
“…Though dissimilar welding has been practiced for many high temperature tubular applications, failures have been reported in these welds [6,7]. Laha et al [7] reported inferior stress rupture properties of dissimilar welds of Cr-Mo steels with austenitic stainless steels compared to the base metal counterparts [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations